The impact of prenatal psychologic and obstetric parameters on postpartum depression in late-term pregnancies: A preliminary study - Derya Akdag Cirik; Neslihan Yerebasmaz; Vahap Ozan Kotan; Kerime Nazli Salihoglu; Funda Akpinar; Serdar Yalvac; Omer Kandemir (Elsevier, 2016)
Objective: To determine the prenatal psychologic (anxiety and depression) and perinatal obstetric (pregnancy and labor complications) predictors of postpartum depression (PPD) in late-term pregnancies. Materials and methods: A total of 149 women with late-term gestation who were hospitalized for antenatal fetal surveillance were included. All participants were asked to complete Hospital Anxiety and Depression Scale immediately after hospitalization and Edinburgh Postnatal Depression Scale in the postpartum period. Demographic, psychologic, and obstetric variables were tested as predictors of PPD by regression analysis. Results: High scores for prenatal anxiety, depression, and PPD were detected in 17.4%, 12.8%, and 23.5% of the participants, respectively. The mode of delivery was not associated with PPD for late-term pregnancies. Women having urgent cesarean, planned cesarean, and vaginal delivery had similar rates of PPD (28.1%, 23.8%, and 21.9%, respectively). In the multivariant analysis, prenatal depression [odds ratio (OR), 9.85; 95% confidence interval (CI), 2.72-35.65], prenatal anxiety (OR, 4.95; 95% CI, 1.59-15.39) and suspicion of fetal distress (OR, 4.44; 95% CI, 1.13-13.64) were found to be independent predictors of PPD. Conclusion: For late-term pregnancies, women with prenatal anxiety or depression and had cesarean delivery due to the suspicion of fetal distress were at risk for PPD.